Multistep closed-loop power control using linear receivers for DS-CDMA systems. - Lian Zhao (IEEE Transactions on wireless communications)
A closed-loop power control strategy, which includes both power control and power allocation functions, for a code-division multiple-access system is proposed. The target power level for a minimum mean squared error (MMSE) or a matched filter (MF) linear receiver is iteratively computed, and the power control command (PCC) is generated by comparing the received power with the generated target power. The PCC history and the channel fade slope information, which contains the Doppler effect, are used to generate variable stepsizes for regulating the transmit power level. Closed-loop power control is based on a criterion that minimizes the average transmit power and the standard deviation of the received power/signal-to-interference ratio. The power control strategy also tends to reduce the bit error rate. Simulation results demonstrate the effectiveness of the proposed power control algorithm. The results also indicate that the tracking ability of the MMSE and MF receiver is essentially similar, except that the average transmit power is lower with the MMSE receiver but is more complex to implement.